2016
DOI: 10.3897/bdj.4.e10084
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria of Greece: an annotated checklist

Abstract: BackgroundThe checklist of Greek Cyanobacteria was created in the framework of the Greek Taxon Information System (GTIS), an initiative of the LifeWatchGreece Research Infrastructure (ESFRI) that has resumed efforts to compile a complete checklist of species reported from Greece. This list was created from exhaustive search of the scientific literature of the last 60 years. All records of taxa known to occur in Greece were taxonomically updated.New informationThe checklist of Greek Cyanobacteria comprises 543 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 57 publications
3
13
0
Order By: Relevance
“…Corresponding morphotypes have been recently reported from Greece (Gkelis et al. , Lamprinou et al. ), Germany (Schulz et al.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Corresponding morphotypes have been recently reported from Greece (Gkelis et al. , Lamprinou et al. ), Germany (Schulz et al.…”
supporting
confidence: 63%
“…Cells are mostly shorter than wide and often have many necridia (Kom arek and Anagnostidis 2005). Corresponding morphotypes have been recently reported from Greece (Gkelis et al 2013, Lamprinou et al 2013, Germany (Schulz et al 2016), Bulgaria (Uzunov et al 2008), Ukraine (Vinogradova and Mikhailyuk 2009), India (Kushwaha and Tiwari 2017), and Africa (Dojani et al 2013). This morphotype also has been found in the Americas with reports from the Mojave Desert soils in California (Alwathnani and Johansen 2011) as well as for Atacama Desert soils in Chile (Patzelt et al 2014).…”
supporting
confidence: 59%
“…The polyphasic taxonomy applied to the strains of this study revealed taxa known to be part of bloom-forming communities ( Sphaerospermopsis and Nodularia), rock-dwelling communities ( Scytonema and Tolypothrix ), and hot spring cyanobacteria mats ( Desertifilum and Gloeotrichia ) (Dadheech et al, 2014; Mazur-Marzec et al, 2015; Gkelis et al, 2017; Joanna and Andrzej, 2018). Our results revealed the presence of taxa not previously described from Greek habitats (Gkelis et al, 2016), such as Allinostoc (Saraf et al, 2018) and Oculatella (Osorio-Santos et al, 2014) and taxa previously described only from the tropical zone like Komarekiella and Kovacikia (Miscoe et al, 2016; Hentschke et al, 2017). Furthermore, the Geitleria calcarea strain isolated in this study, to the best of our knowledge, is the first isolate in world’s cyanobacteria culture collections depositories (Friedmann, 1979; Coute, 1989), whilst Chlorogloea sp.…”
Section: Discussionsupporting
confidence: 59%
“…The scarce records of Nodularia across Mediterranean could be linked with the absence of a high number of brackish environments. Anagnostidis (Anagnostidis, 1968),decades ago, reported the occurrence of N. spumigena and N. harveyana in Greece, (Gkelis et al, 2016). The largest research activity on the genus Nodularia occurs on the Baltic Sea, where Nodularia spumigena forms highly toxic blooms with significant effects on aquatic and non-aquatic organisms (Sivonen et al, 1989; Finni et al, 2001; Mazur-Marzec et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In Greece, the occurrence of more than 35 Leptolyngbya taxa has been reported from various habitats (Gkelis et al. ). Moreover, our recent research on sponge‐associated cyanobacteria in the North Aegean Sea (Konstantinou et al.…”
mentioning
confidence: 99%